Evaluating the risk of bovine tuberculosis posed by standard inconclusive reactors identified at backward-traced herd tests in Northern Ireland that disclosed no reactors. (July 2022) - Georgaki, Anastasia; Bishop, Hannah; Gordon, Alan; Doyle, Liam; O'Hagan, Maria; Courcier, Emily; Menzies, Fraser
Abstract: Bovine tuberculosis is a notifiable disease in Northern Ireland with the national eradication programme of compulsory testing and slaughter of reactor animals costing approximately £40 million per year. Backward tracing, known as Backward Check Tests (BCTs), of reactor animals is used to identify previous herds where the bTB positive animal has resided. The aim of this study was to quantify the bovine tuberculosis (bTB) risk posed by inconclusive reactors (ICs) at BCTs at both the individual animal and the herd level. ICs to the Comparative Intradermal Tuberculin Test (CITT) at a BCT, in which no reactors were found, were matched with CITT negative animals, based on age, sex, test ID and follow up period, in Northern Ireland between 1st January 2008 and 31st December 2017 (inclusive). A retrospective matched cohort study design was used with the outcome of interest being the bTB status of each animal and subsequent bTB herd breakdowns. After adjusting for herd size, IC animals at a BCT had 16 times the odds (95% confidence interval: 7.75 to 38.28, p < 0.001) of becoming bTB positive compared to CITT negative animals. The percentage population attributable risk was 0.0001%. The majority 75% ( n = 71) of ICs that became bTB positive were identified at the 42 day retest. Of those that were not disclosed at the 42 day retest ( n = 24), almost a third (29%) had moved to an unrestricted herd. However, after adjusting for herd size and type, herds that had ICs only identified at a BCT did not have an increased odds of a subsequent bTB herd breakdown compared to herds that had a CITT negative BCT. Given the increased risk posed by ICs at a BCT, it may be justifiable to remove them from the herd immediately or place them under lifetime movement restrictions to the herd where they were detected. However, further action regarding the herd of origin does not appear to be justified. Highlights: Inconclusives at backward trace tests have a higher odds of becoming bTB positive. A quarter of inconclusives, which became bTB positive, were missed at the re-test. Lifetime restriction of inconclusives to the disclosing herd may be justifiable. ICs only at a backward trace test did not increase the odds of a bTB herd breakdown. Further action regarding herds with ICs may not be necessary.